2022
DOI: 10.1111/ijfs.16112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen‐rich water on the nutritional properties, volatile profile and texture of germinated brown rice

Abstract: Summary In the present study, we investigated the effects of hydrogen‐rich water (HRW) on the germination efficiency, chemical composition, biofunctional and volatile compounds, and texture of germinated brown rice (GBR). Our results showed that HRW (1.5 mg L−1) treatment significantly increased the germination efficiency of GBR by changing the migration of water during soaking. A chemical composition analysis showed that HRW treatment changed the contents of some biofunctional compounds and volatile component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Researchers have also reported that, during soaking in water, the germ of GBR produces substances both physiologically and through the action of enzymes which improve the nutritional value and the texture of brown rice [ 11 , 12 ]. Zhu et al [ 13 ] investigated the effects of hydrogen-rich water (HRW) on the germination efficiency and texture of GBR and found that HRW (1.5 mg L −1 ) treatment significantly increased the germination efficiency of GBR by changing the migration of water during soaking and also improved the texture of GBR due to changes in the ultrastructure of the bran layer and a decrease in insoluble dietary fiber. In addition, subjecting germinated brown rice to microwave precooking and freeze-drying treatments made the brown rice softer, with hardness reduced by about 54.78% after treatment, and also easier to chew, as the chewiness of the precooked brown rice was lowered [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also reported that, during soaking in water, the germ of GBR produces substances both physiologically and through the action of enzymes which improve the nutritional value and the texture of brown rice [ 11 , 12 ]. Zhu et al [ 13 ] investigated the effects of hydrogen-rich water (HRW) on the germination efficiency and texture of GBR and found that HRW (1.5 mg L −1 ) treatment significantly increased the germination efficiency of GBR by changing the migration of water during soaking and also improved the texture of GBR due to changes in the ultrastructure of the bran layer and a decrease in insoluble dietary fiber. In addition, subjecting germinated brown rice to microwave precooking and freeze-drying treatments made the brown rice softer, with hardness reduced by about 54.78% after treatment, and also easier to chew, as the chewiness of the precooked brown rice was lowered [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…After germination, the contents of VOCs of n-hexane, isoheptane, octamethylcyclotetrasiloxane, o-xylene, ether, methyl 2-methylbutyrate, 1-hexanol, 3-heptanol, and 2,5-dimethyldecane were increased significantly. In the GQ samples, 1-hexanol and 3-heptanol, producing flower, banana, and herb odors, might be formed from lipid oxidation catalyzed by alcohol reductase ( Zhu et al, 2022 ). Methyl 2-methylbutyrate, producing fruit and strawberry aromas, might be produced by the esterification of alcohols and acids.…”
Section: Resultsmentioning
confidence: 99%